Adenocarcinoma with Neuroendocrine Differentiation of the Colon Accompanying Osteoclast-Like Giant Cells - Mitsuhiro Tachibana; Tadahiro Isono; Yutaka Tsutsumi (Case Reports in Pathology)
Introduction. Neuroendocrine differentiation in colorectal cancer is reportedly associated with poorer grade of tumor differentiation, nodal and distant metastasis, and other unfavorable features, contributing to a worse clinical outcome. Colorectal cancer with osteoclast-like giant cells (OGCs) is extremely rare. Case Presentation. An 86-year-old woman was diagnosed as double cancer of the transverse and sigmoid colon. Both tumors were simultaneously removed. The transverse colon cancer directly invaded the area of the right gastroepiploic vessels and spread to the nodes and histologically consisted of both the tubuloglandular and solid components. CD8/granzyme B-positive tumor-infiltrating lymphocytes and CD163/CD68-positive macrophages, frequently forming OGCs, were observed particularly at the invasion front. The carcinoma cells were labeled focally for synaptophysin and diffusely for the DR locus of the human leukocyte antigen and programmed death-ligand 1 (PD-L1). Deficient expression of DNA mismatch repair (dMMR) proteins was immunohistochemically confirmed. The patient died 16 months after surgery. Conclusion. This is the first report of colonic adenocarcinoma with neuroendocrine differentiation accompanying OGCs. Histopathologic factors of the poor prognosis in the present case included (a) the presence of more than 2% cells with neuroendocrine differentiation, (b) infiltration of CD163/CD68-positive OGCs at the invasion front, (c) deficiency of dMMR proteins, and (d) PD-L1 expression.